KIAA1199 Biomarker and Ultrasonographic Findings in Rheumatoid Arthritis Patients and their Correlation with Disease Activity - Selim, Zahraa Ibrahim; El-Hakeim, Eman H; Omran, Eman Ahmed Hamed; Idriss, Naglaa K.; Gaber, Marwa A.; Ross, Sylvia V (Aktuelle Rheumatologie, 2018)
Introduction Rheumatoid arthritis (RA) is an autoimmune disease that affects multiple joints causing joint destruction. KIAA1199 is a novel angiogenic biomarker derived from fibroblast-like synoviocytes (FLS) it has a role in acceleration and proliferation of FLS and activation of angiogenic signaling pathways leading to erosion of cartilage and bone. Musculoskeletal ultrasound (MUSU) and Power Doppler (PDUS) directly visualizing the synovial membrane vessels, which is important in providing very early information on the changes in synovitis activity during the course of the inflammatory joint diseaseObjective To assess the serum level of angiogenic biomarker KIAA1199 in RA patients and its correlation with MSUS, PDUS findings, and the disease activity Patients and methods: Fifty RA patients and 40 healthy control persons age and sex-matched were recruited in this study, KIAA1199 was assessed in the serum of patients and controls, MSUS and PDUS were done for the wrist, elbow, and knee joints for all RA patientsResults Serum KIAA1199 level was significantly higher among RA patients 4.36±1.22 ng/dl compared to control group 2.87±0.51 ng/dl (p<0.001). There was a highly significant correlation between KIAA1199 level and DAS28 (p=0.004), and there was a significant correlation between the PDUS with KIAA1199 level and DAS28 (p=0.001, 0.002 respectively) in wrist jointsConclusion KIAA1199 is a new pathway that enhancing cell proliferation and angiogenesis. Serum KIAA1199 level may be a useful biomarker for RA activity, and therapeutic target in RA. PDUS correlates significantly with clinical findings and novel angiogenic biomarker in RA patients.
Keywords: KIAA1199; Power Doppler Ultrasound (PDUS); Rheumatoid Arthritis (RA)